Kupi II Congress and Results of Religious Views on Contemporary Women's Issues in the Perspective of Islamic Anthropology - Arwani, Salsabila; Hannase , Mulawarman (Borong Newinera Publisher, 2024)
This paper is a study related to the Indonesian Women's Ulama Congress (KUPI) and its religious views through an Islamic feminist anthropology approach. This is because the discussion on KUPI hasn’t been captured through this approach. In fact, by this approach, the problems surrounding women can be seen in more depth and detail. By using primary data from observations and secondary data from literature reviews, the results found that KUPI or the Indonesian Women's Ulama Congress is a women's organization in Indonesia that brings together various individual backgrounds to study women's problems based on Islamic teachings that are mutabadil. Through discussions, halaqoh and religious meetings, the first KUPI congress in Cirebon produced three religious views while the second congress in Jepara produced five religious views and several recommendations regarding the protection of women from religious extremism, forced marriages, dangers of pregnancies due to settlement, genital injuries, and issues environment. KUPI activities are cultural in nature. Participants who come from various backgrounds bring facts and data in the field to be interacted with in order to realize human reason, mind and power which then shape culture and find an Islamic religion that is moderate, gender fair and provides human welfare.